PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN SERTA IMPLIKASINYA TERHADAP LOYALITAS PELANGGAN PT. LATAHZAN WISATA NUSA - Arni Kurniati; Siti Nurkhasanah (Fakultas Ekonomi Universitas Borobudur, 2022)
Abstract This study aims to determine the extent of the influence of service quality and promotion on customer satisfaction and its implications for customer loyalty. The data used in this study are primary data collected from respondents' answers based on the questionnaire given, as many as 98 people. The data processing method uses the Path Analysis method with the help of SPSS version 21.0. Statistical testing using individual parameter significance test (t test) and simultaneous significance test (F test). The results showed that simultaneously the variables of service quality, promotion and customer satisfaction had a significant effect on customer loyalty. Partially shows that analysis 1: service quality variable has a significant effect on customer satisfaction performance, while analysis 2: promotion variable has a significant effect on customer satisfaction and in analysis 3: customer satisfaction variable has a significant effect on customer loyalty. Keywords: Service Quality, Promotion, Customer Satisfaction and Customer Loyalty